And What About the Family Back Home? International Migration and Happiness - Fernando Borraz; Susan Pozo; Máximo Rossi (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
In this study we use data on subjective well being and migration in Cuenca, one of the Ecuador's largest cities. We examine the impact of migration on the happiness of the family left behind. We use the propensity score matching estimator to take into account the endogeneity of migration. Our results indicate that migration reduces the happiness of those left behind. We also find that the monetary inflows (remittances) that accompany migration do not increase happiness levels among recipients. These results suggest that the family left behind cannot be compensated, for the increase in unhappiness that it sustains on account of the emigration of loved ones, with remittances from abroad.
Keywords: A12; F22; I31; 330; Happiness; migration; remittances